Class, Style and Territory in the Drari Microcultures of Brussels - Mattias De Backer (Societies, 2019)
Much like Parsons’s notion of “youth culture,” the tradition of subculture developed by the Birmingham School was criticised as being too romantic, too general, and too dependent on a simplistic model based on the inside/outside binary. Since the 1990s, “post-subcultural” studies have developed which prefer to focus on agency rather than structure. A “third school” of youth cultural studies focused on medium sizes groups and their attachment to place, which they called “microcultures”. This paper, drawing from fieldwork undertaken in Brussels between 2013 and 2016 with young people, studies members of the Brussels “street culture” called the drari, while zooming in on the combinations of personalities, the events they share and the locations they make their own. Specifically, this paper argues that the drari microculture does not fit in the binary model of (post-)subcultural theory, nor in the criminological frame of urban youth gangs, by focusing on the affective and class-related phenomena internal to their practices of territory-building.